Consumption of Aloe vera Mucilage Attenuates Plasma Oxidative Stress and Dyslipidemia in Type 2 Diabetic Rats - ZhongKai Zhou; Xiaochong Ren (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2015)
Diabetes is one of the most costly and burdensome chronic diseases, which gains increasingly public health concern. More importantly, hyperglycemia is also accompanied by hyperlipidemia.Nowadays the agents used for diabetes treatment are mainly synthetic drugs and insulin. However, these drugs usually come with considerable side effects, such as hypoglycemia, drug-resistance,dropsy and weight gain. Thus, it is not surprising there is a great interest in novel approaches to Diabetes Mellitus (DM) management.In particular, there has been an increasing demand for natural products, and A. vera is one of them currently showing the potentials in this field.A. vera leaves are consisted of chlorenchyma cells and thinner walled cells forming the parenchyma (filets).The parenchyma cells contain a transparent mucilaginous jelly which is referred to as Aloe vera gel.The gel has been widely accepted since the 4th century B.C. as a traditional medicine. The majority of the mucilaginous is acemannan,an acetylated glucomannan. The polysaccharide has been shown the potential to be an immunostimulant for enhancing the immunologic functions [1].